Hydrothermal liquefaction of bagasse using ethanol and black liquor as solvents. (10th September 2015) - Kosinkova, Jana; Ramirez, Jerome A.; Nguyen, Jenny; Ristovski, Zoran; Brown, Richard; Lin, Carol S.K.; Rainey, Thomas J.
Abstract: The objective of this study was to examine the hydrothermal liquefaction of sugarcane bagasse using ethanol and black liquor (BL) in a pilot scale. Combinations of co‐solvents (ethanol/water, ethanol/BL) were studied at various concentrations and reaction conditions. The maximum oil yield of 61% was achieved with a reaction temperature of 300 °C for 30 min and using pure BL as a solvent, while the highest higher heating value (HHV) was obtained from a 50:50 ethanol‐BL mixture. The oils contained alcohols, esters, phenolic compounds, aromatics, and heterocyclics. The O/C and H/C ratios of the oil were comparable with traditional biodiesel and commercial diesel. Although this study showed there are some improvements to be made to improve the chemical composition, the approach has potential for large‐scale production of a substitute for fossil‐fuel‐based diesel. © 2015 Society of Chemical Industry and John Wiley & Sons, Ltd